Rahasia Sukses Kebab abud's dalam Kepemimpinan yang Tangguh dalam Bisnis Kuliner Cabang Marapalam Padang - Vivi Nila Sari; Annisa Syarah; Inka Februslita; Rosi Nifrianti; Sandya Pramunitia (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This article aims to explore the relationship between bonuses given to employees and their performance in a kebab business. Its main focus is to determine whether fair and profitable bonuses can motivate employees to work harder and increase their productivity. In this case, it will involve the role of the leader in distributing bonuses to employees in a transparent and objective manner.